Univerzalni sporočilni sistem - Ojsteršek, Milan (Uporabna informatika (Ljubljana), 1999)
Unified Messaging System allows integration of various messaging systems and messaging media into a complete integrated messaging sustem. Such a sustem includes electronic, voice, fax messages and wireless access to the user mailbox. The sustem offers access to the all types of messages anythere and anytime through various communication software and devices like e-mail clients, web browsers, phones, mobile phones and fax devices.
Keywords: elektronsko poslovanje; informacijska tehnologija; sporočila; telekomunikacijska tehnika